The influence of cortisol co-secretion on clinical characteristics and postoperative outcomes in unilateral primary aldosteronism - Jiang, Yiran; Zhou, Lihua; Zhang, Cui; Su, Tingwei; Jiang, Lei; Zhou, Weiwei; Zhong, Xu; Wu, Luming; Wang, Weiqing (Frontiers in Endocrinology, 2024)
Context: The prevalence of unilateral primary aldosteronism (UPA) with cortisol co-secretion varies geographically. Objective: To investigate the prevalence and clinical characteristics of UPA with cortisol co-secretion in a Chinese population. Design: Retrospective cohort study. Methods: We recruited 580 patients with UPA who underwent cosyntropin stimulation test (CST) after the 1-mg dexamethasone suppression test (DST) and retrospectively analyzed the clinical characteristics and postoperative outcomes of UPA with and without cortisol co-secretion. Results: UPA with cortisol co-secretion (1 mg DST>1.8 ug/dL) was identified in 65 of 580 (11.2%) patients. These patients were characterized by older age, longer duration of hypertension, higher concentration of plasma aldosterone and midnight cortisol, lower adrenocorticotropic hormone (ACTH) and dehydroepiandrosterone sulfate (DHEAS), larger tumor diameter, and more history of diabetes mellitus. Cortisol and aldosterone levels were higher and DHEAS level was lower in UPA with cortisol co-secretion at 0–120 min after CST. Among 342 UPA patients with KCNJ5 gene sequencing and follow-up results, the complete clinical success rate was lower in UPA with cortisol co-secretion (33.3% vs. 56.4%, P<0.05); the complete biochemical success rate and KCNJ5 mutation did not differ between the two groups. Age, tumor size, and ACTH were independent predictors of UPA with cortisol co-secretion. Sex, BMI, duration of hypertension, KCNJ5 mutation, and cortisol co-secretion were independent predictors for complete clinical success in UPA after surgery. Conclusions: UPA with cortisol co-secretion is not uncommon in China, but the clinical features were distinctly different from those without co-secretion. Cortisol co-secretion is an independent risk factor for incomplete clinical success after surgery in UPA.